Respuesta :

The sum is 4x³ + 3x² + 2x – 6.

Solution:

The correct question is given below.

(4x³ – 2x² + 3x – 1) + (5x² – x – 5). What is the sum?

To find the sum of the polynomial:

Sum of (4x³ – 2x² + 3x – 1) and (5x² – x – 5)

           = (4x³ – 2x² + 3x – 1) + (5x² – x – 5)

Remove the parentheses.

           = 4x³ – 2x² + 3x – 1 + 5x² – x – 5

Group like terms together.

           = 4x³ – 2x² + 5x² + 3x – x – 1 – 5

Add the similar elements. i.e the element with same power.

           = 4x³ + 3x² + 2x – 1 – 5

Subtract the constant terms.

           = 4x³ + 3x² + 2x – 6

The sum is 4x³ + 3x² + 2x – 6.

ACCESS MORE